Genetic Polymorphism of N-acetyltransferase 2 (NAT2) among Patients with Tuberculosis: A Scoping Review of the Indonesian Studies - Putra, Oki Nugraha; Ramadhani, Sylvia Rizki; Yulistiani, Yulistiani; Julaeha, Julaeha; Hidayatullah, Affan Yuniar Nur (Sciences of Pharmacy, 2026)
The distribution of N-acetyltransferase-2 (NAT2) genetic polymorphisms varies across ethnic groups among Indonesian TB patients. This review aimed to provide a comprehensive understanding of the prevalence of NAT2 genetic polymorphisms and their association with DILI and isoniazid pharmacokinetics in Indonesian TB patients. A scoping review was conducted by searching Google Scholar, Scopus, and PubMed in accordance with PRISMA guidelines for scoping review (PRISMA-ScR). We retrieved 668 studies from three databases and we enrolled 12 studies for final analysis. Eleven studies reported on adult TB patients and one study on pediatric TB patients. Overall, the available evidence suggests that the slow acetylator phenotype is relatively common among TB patients in Indonesia, although its distribution varies across regions and ethnic groups. The NAT2*6 polymorphism was frequently observed among TB patients with a slow acetylator phenotype. TB patients with slow acetylation exhibited higher serum concentrations of isoniazid, which were significantly associated with an increased risk of DILI. No studies reported an association between NAT2 genetic polymorphisms or acetylation status and treatment outcomes among TB patients. This review confirms substantial variation in NAT2 genetic polymorphisms across studies in Indonesia. TB patients with a slow acetylator phenotype appear to have a greater risk of developing DILI compared with those with intermediate or fast acetylator phenotypes. Information on acetylator status may identify patients at higher risk of hepatotoxicity, particularly those with the slow acetylator phenotype. Therefore, integrating NAT2 pharmacogenetics into clinical practice may predict hepatotoxicity and optimize tuberculosis therapy.